Neo-tribes and Antarctic expedition cruise ship tourists - Kriwoken, L; Anne Hardy (2018)
Recent research has explored the size and nature of the cruise ship industry and to a lesser extent the impacts of social interaction upon the experiences of individuals while cruising. However, there is little research that examines the performative aspects of social groups that form as a result of social interaction. Using a neo-tribal lens, we examine this phenomenon in the context of passengers on board an Antarctic expedition cruise ship. The neo-tribal lens offers insights into the lifestyles, sense of belonging, rituals and meeting places that form amongst groups of passengers. This research progresses the conceptualization of neo-tribes by suggesting that neo-tribes are a phenomenon that may occur in confined, liminal places. In doing so it advances an understanding of the outcomes of the cruise ship experience by looking past individualistic outcomes, to the behavioural aspects that can result from undertaking a cruise ship holiday in Antarctica.